Hybrid Enterprise / Mohamad Fairulnizam ... [et al.] - Mohamad Hassan, Mohamad Fairulnizam; Mohamad Sukri, Mohamad Fazari; Asmee, Rodhuan; Ismail, Daud (2004)
Hybrid Enterprise is a new company that offer a computer products and services.The main of our business Hybrid Enterprise is to fulfil the business opportunity. Our target customers are students and publics. We also give the quality service maintenance and accessories hardware. The business operate in Shahab Perdana, Alor Setar, Kedah.